PENGARUH LAMA PERENDAMAN DALAM AIR TERHADAP SITOTOKSISITAS FIBER REINFORCED COMPOSITE JENIS POLYETHYLENE FIBER PADA SEL FIBROBLAS (METODE MTT) - , SHERLY HERLIANTI PUTRI A ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Fiber reinforced composite (FRC) is a material made of polymer matrix that is reinforced by fibers. Polyethylene fiber is one of the commonly used fiber due its good properties. The use of FRC in the oral cavity promotes a sustainable interaction between the FRC and saliva which is mostly consists of water. Polymer matrix absorbs water and facilitate a monomer release which can cause a cytotoxic effects to human cells. The purpose of this study was to determine the effect of immersion duration in water to cytotoxicity of polyethylene FRC on fibroblasts. Flowable composite (MasterFlow, Biodinamica, Brazil) and polyethylene fiber (CONSTRUCT Kerr) are material used in this study. Samples which sized 2x2x5 mm (n=8) immersed in 2 ml of water for 0,1,and 7 days. The water extracts were added in to the culture of fibroblast cells (Vero cell line). Cytotoxicity test were done by using the MTT method. The optical density was calculated using the ELISA Plate reader to determine the percentage of surviving cells. Data were statistically analyzed by One Way ANOVA and LSD0.05. The results showed an average viability of fibroblasts of the water immersion group (0,1,7 days) were86.713+2.297%, 77.082+3.388%, 74.079+3.350%. The viability of fibroblasts were decreased from day 0 to day 7. The result of One Way ANOVA test showed a significant influence between immersion duration and viability of fibroblasts (p<0.05). LSD0.05showed significant differences between treatment groups except 1 and 7 days (p>0.05). The conclusion of this study: immersion duration of Polyethylene FRC has significant effect against cytotoxicity on fibroblast. Keyword: polyethylene FRC, water immersion, cytotoxicity, MTT method, fibroblast